The new definition of metabolic dysfunction-associated steatotic liver disease: the role of ultrasound and elastography - Xinrui Jin; Terry Cheuk-Fung Yip; Grace Lai-Hung Wong; Vincent Wai-Sun Wong; Jimmy Che-To Lai (Ultrasonography)
In 2023, nonalcoholic fatty liver disease was renamed metabolic dysfunction-associated steatotic liver disease by the American and European liver associations. This new nomenclature recognizes metabolic dysfunction as the central driver of the disease, and the diagnostic criteria now require the presence of hepatic steatosis plus at least one of five cardiometabolic risk factors. B-mode ultrasonography remains the most common and practical method for detecting hepatic steatosis, although newer ultrasound techniques based on attenuation, backscatter, and speed of sound have gained traction as tools to diagnose and quantify hepatic steatosis. Additionally, ultrasound elastography is increasingly used in routine clinical practice to assess liver fibrosis, diagnose cirrhosis, and identify clinically significant portal hypertension.